Race and Place: Hollywood’s Vision of Urban Youth in Los Angeles Film - Marika Piday-Warren; David E. James (American Studies Journal, 2010)
This paper examines films about youth of the late 1980s and 1990s in Los Angeles. While focusing on the analytical categories of space and race, the paper underscores the importance of historicizing and contextualizing the genre. Thus, it stresses the significance of successive waves of different ethnic immigration and argues that these created distinct enclaves, many of them internally homogenous in terms of race and class. The distinct enclaves both prepared the ground for the formation of the polynucleated and decentered modern megalopolis and influenced Hollywood’s vision of urban youth.